Pequenas constelações culturais: projetos educativos e a formação permanente - Moraes, Edson Martins (2021)
The main objective of this work is to analyze the non-formal education projects and how the training processes of the managers who work in the following cultural spaces occur: Project Marieta, Cia Circo dance Suzie Bianchi, Ateliê Fon Fin Fan, Casa Amálgama, Casa Constantina, Casa da Ponte and Casa Rocha 259. With the purpose of highlighting the convergence of formal education, non-formal education and informal education in the programs of educational institutions spread all over the country were used, in the first chapter of this work, the following theoretical references: (LIBÂNEO, 2010); (GOHN, 2006, 2007, 2011); (GASPAR, 2002); (PARK, 2005); (AFONSO, 2001); (APPLE, 2001, 2017); (MOREIRA, SILVA, 1995); (SILVA, 2010); (NOVOA, 2013, 2020); (TRILLA, 1993, 2008); (GARCIA, 2005, 2007); (FREIRE, 2018, 2007). The concepts of culture and the training of cultural managers are addressed in the second chapter based on the following authors: (EAGLETON, 2011); (LARAIA, 2009); (VELHO, 1994); (FREIRE, 1987, 2011, 2015); (BRANDÃO, 2017); (SANTOS, 2012); (CUNHA, 2012); (LIBÂNEO, 2005); (NOVOA, 2013); (VELHO, 1994); (GOHN, 2011); (BARROS, 2011); (DURAND, 2013); (FELDMANN, 2009); (GARCIA, 1999). The methodology used in this dissertation is defined as qualitative with documental analysis, bibliographical research, followed by discursive textual analysis, the work also expresses our direct contact with the investigated situation and with the participants. The raw material for the construction of this research was conceived through texts, the result of manager meetings transcripts that took place at the Research and Training Center of Sesc São Paulo. The following criteria were adopted to mention the four cultural managers: “Sesc Cultural Management Course” graduates; non-formal education organizers; Sesc São Paulo Research and Training Center programs participants and their activities in cultural spaces. The texts, the use of a discursive textual analysis and the theoretical framework of this research show us that the managers of these spaces seek recognition of their institutions as educational places, they transmitted ancestral knowledge, they are in constant formation in order to improve their actions. Cultural spaces are project laboratories which provide experiences that remain imbued in the body and contribute to transforming territories into stories places, where people move and share collective values as protagonists of their own inventions, creators of their own culture